2020
DOI: 10.1007/s13201-020-01237-9
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Procion Red MX-5B dye from aqueous solution using homemade peach and commercial activated carbons

Abstract: Wastewater treatment is of great concern in the textile industries because dyes, which are released into wastewater, are stable due to their structures and that some of the existing conventional techniques are not effective for aqueous removal of dyes. Among the advanced techniques for treatment of industrial effluents, adsorption is one of the most effective processes for removal of dyes from industrial wastewater. Similarly, activated carbons from different sources have been successfully applied as adsorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Further adsorbed quantity rises more slowly as the surface become saturated with the adsorbate. Similar adsorption behavior was reported for nitrate [62] and dye molecules removal [63].…”
Section: Kinetic Studiessupporting
confidence: 84%
“…Further adsorbed quantity rises more slowly as the surface become saturated with the adsorbate. Similar adsorption behavior was reported for nitrate [62] and dye molecules removal [63].…”
Section: Kinetic Studiessupporting
confidence: 84%
“…As reported in Nazifa et al [16], the use of activated carbon from corncob to remove Procion Red resulted in a maximum adsorption capacity of 2.86 mg g -1 . Another research by Sarma et al [17] using montmorillonite to remove Procion Red produced a maximum adsorption capacity of 11.09 mg g -1 , while Procion Red adsorption using commercial activated carbon resulted in a maximum adsorption capacity of 167 mg g -1 at 273 K [18]. Biosorbent from modified avocado shells was also found to be highly effective for Procion Red removal, with a maximum adsorption capacity of 167 mg g -1 [19].…”
Section: Introductionmentioning
confidence: 93%
“…The obtained results showed that the adsorption followed the physical adsorption mechanism. Negative values of ΔQ ads showed that the reaction was exothermic (Rao and Khan 2017;Ribas et al 2020).…”
Section: Thermodynamics Studiesmentioning
confidence: 99%